2020
DOI: 10.12659/msm.925278
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinase-2, Matrix Metalloproteinase-9, Tissue Inhibitor of Metalloproteinase-1, and Changes in Alveolar Septa in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background This study investigated the relationship between the pathological alteration of alveolar septa and (1) pulmonary function and (2) matrix metalloproteinase (MMP)-2, MMP-9, and tissue inhibitor matrix metalloproteinase 1 (TIMP-1) expression in chronic obstructive pulmonary disease (COPD). Material/Methods Sixty patients with pulmonary disease were divided into control (n=20) and COPD (n=40) groups. Postoperative lung tissue specimens were examined. Hematoxylin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(30 reference statements)
0
7
0
3
Order By: Relevance
“…When stimulated, COX-2 expression is rapidly upregulated, which can induce acute inflammatory response in humans and animals. MMP-2 and MMP-9 are considered to be important collagenases in inflammatory diseases, and the synthesis and secretion of MMP-2 and MMP-9 are highly related to TNF-α [43]. IL-10 expression can reduce lung neutrophil infiltration and inhibit the expression of TNF-α, IL-6, and MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…When stimulated, COX-2 expression is rapidly upregulated, which can induce acute inflammatory response in humans and animals. MMP-2 and MMP-9 are considered to be important collagenases in inflammatory diseases, and the synthesis and secretion of MMP-2 and MMP-9 are highly related to TNF-α [43]. IL-10 expression can reduce lung neutrophil infiltration and inhibit the expression of TNF-α, IL-6, and MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…The GA and tiamulin treatment were both effective in inhibiting the expression of MG-activated p-ERK, p-JNK, p-p38, and p-jun (Figure ). Downstream MMPs of the MAPK pathway have been demonstrated to be involved in the emergence and progression of various lung diseases. , In chronic obstructive pulmonary disease, pathological changes in the alveolar septum correlate with lung function and MMP-2 and MMP-9 expression levels . Another study demonstrated that MMP2/9 is the predominant regulator of the cytotoxic effects induced by amyloid-β in lung cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…56,57 In chronic obstructive pulmonary disease, pathological changes in the alveolar septum correlate with lung function and MMP-2 and MMP-9 expression levels. 58 Another study demonstrated that MMP2/9 is the predominant regulator of the cytotoxic effects induced by amyloid-β in lung cancer cells. 59 We therefore also examined the expression of MMP2 and MMP9 associated with the lung injury in vivo and in vitro.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Тройную Таблица 1. Основные характеристики пациентов, включенных в исследование 57 (95) 3 (5) 55 (91,7) 5 (8,3) 56 (93,3) 4 (6,7) 0 На момент индексного обострения ХОБЛ в плазме крови пациентов методом твердофазного иммуноферментного анализа определяли маркеры: ■ эозинофильного воспаления: эозинофильный катионный белок (ЕСР), IL-5 [16,23]; ■ нейтрофильного воспаления: нейтрофильная эластаза, гранулоцитарно-макрофагальный колониестимулирущий фактор (GM-CSF) [20,21]: ■ макрофагального воспаления: моноцитарный хемотаксический протеин 1 (МСР-1) [24]; ■ фиброзирования: фактор роста фибробластов 2 (FGF-2), трансформирующий фактор роста бета 1 (TGF-β1), гиалуроновая кислота, N-терминальный пептид проколлагена III типа (PIIINP) [25]; ■ а также уровень матриксных металлопротеиназ (ММР) 1 и 9 изоформ [26], IL-1β, С-реактивного белка (СРБ).…”
Section: материалы и методыunclassified